Comparative Analysis of Motor Skills Between 10-12-Year-Old Boys Volleyball Players and Physically Inactive Peers - Rosita Kiaulakytė; Anelė Katinė (Lithuanian Sports University, 2023)
Background. The gross motor function of team sports athletes is superior to that of peers who do not participate in additional physical activity, but it is not clear to what extent motor skills diﬀer between boys who attend volleyball training and those who do not attend training. The aim. To compare the motor skills and functional stability of the trunk of 10-12-year-old volleyball-playing and physically inactive boys. Methods. 30 subjects, boys aged 10-12, participated in the study. The research group consisted of boys playing volleyball (n=15), the control group - physically inactive boys (n=15). Test tools: Bruininks Oseretsky Motor Skills Profciency Test, 2nd Edition and Matthiass Functional Trunk Stability Test. Results. Boy volleyball players showed signifcantly better results in only three of ten evaluated motor tasks compared to inactive boys: side jumps with legs together (8.07±1.03 points vs. 7.27±0.88, p=0.026) and push-ups (5.93±1.28 points vs. 4.53±0.99, p=0.002), and V-up (4.73±1.28 points vs. 3.20±1.27, p=0.009). The result of functional stability test was better in volleyball players than in non-players (24.67±9.26 points vs. 16.53±9.34, p=0.013). Conclusions. Boys who play volleyball had signifcantly better motor skills in strength and agility tasks compared with boys who are physically inactive. No signifcant diﬀerences were found in bilateral coordination, balance and upper extremity coordination tasks between volleyball players and physically inactive boys, but the functional stability of the trunk of boys who play volleyball was signifcantly better than that of physically inactive boys. Keywords: motor skills, functional trunk stability, volleyball, physically inactive